The Antarctic silverfish : a keystone species in a changing ecosystem - Vacchi, Marino; Pisano, E. 1951-; Ghigliotti, Laura (Springer, 2017)
This book encompasses the body of available scientific information on the notothenioid fish Pleuragramma antarctica commonly known as Antarctic silverfish. This plankton-feeder of the intermediate trophic level is the most abundant fish in the coastal regions of high Antarctica, and plays a pivotal ecological role as the main prey of top predators like seals, penguins, whales and Antarctic toothfish. Broad circum-polar distribution, a key role in the Antarctic shelf pelagic ecosystem, and adaptations makes understanding the species' likely response to environmental change relevant to foresee the potential responses at the local ecosystem level. Additionally, a detailed understanding of the abundance and trophic interactions of such a dominant keystone species is a vital element of informing the development of marine spatial planning and marine protected areas in the Antarctic continental shelf region. Experts in the field provide here unique insights into the evolutionary adaptation, eco-physiology, trophic ecology, reproductive and population ecology of the Antarctic silverfish and provide new clues about its vulnerability in facing the challenges of the ongoing environmental changes.
Keywords: Nototheniidae -- Ecology -- Antarctic Ocean.; Nototheniidae -- Antarctic Ocean.; Keystone species -- Antarctic Ocean.; Marine ecology -- Antarctic Ocean.; Antarctic Ocean.; elektronické knihy; electronic books